Probiotics in human health and disease: from nutribiotics to pharmabiotics - Lee, Eun-Sook; Song, Eun-Ji; Nam, Young-Do; Lee, So-Young (The journal of microbiology, 2018)
Probiotics are the most useful tools for balancing the gut microbiota and thereby influencing human health and disease. Probiotics have a range of effects, from those on nutritional status to medical conditions throughout the body from the gut to non-intestinal body sites such as the brain and skin. Research interest in probiotics with nutritive claims (categorized as nutribiotics) has evolved into interest in therapeutic and pharmacological probiotics with health claims (pharmabiotics). The concept of pharmabiotics emerged only two decades ago, and the new categorization of probiotics to nutribiotics and pharmabiotics was recently suggested, which are under the different regulation depending on that they are food or drug. Information of the gut microbiome has been continuously accumulating, which will make possible the gut microbiome-based healthcare in the future, when nutribiotics show potential for maintaining health while pharmabiotics are effective therapeutic tools for human diseases. This review describes the current understanding in the conceptualization and classification of probiotics. Here, we reviewed probiotics as nutribiotics with nutritional functions and pharmabiotics with pharmaceutic functions in different diseases.